"TARIXI SHAVQI" IS AN IMPORTANT WORK: DISCOVERY AND SCIENTIFIC ANALYSES (Scientific journal of the Fergana State University, 2023)
The article is about the discovery and content of the work "Tarihi Shavqi" on the history of the last periods of the Kokand Khanate. The author of the work Shamsiddin Shavqi (1805-1887), served as a munshi (secretary - head of the office of clerks) in the palace of the Kokand Khanate. Although Zaki Walidi Tugan gave preliminary information about the manuscript, he wrote that the manuscript was "in the hands of the population". Historians such as Charles Storey, T. Beisembiev, Sh. Vakhidov, who referred to this work, noted that the manuscript is "in the hands of the people" or "has not yet been found." It is indicated that the manuscript has been preserved in the private collection of Ismail Khoja Lutfitdinov (born 1968), a resident of the village of Kalvak, Turakurgan district, Namangan region. The work is a historical, poetic work about the last days of the Kokand Khanate and the conquest of Ferghana by the Russian Empire.